Five Trade Traders Business Gives Entrepreneurship In The Borderland Area - Hapsari, Veneranda Rini; Ayustia, Rissa; Vuspitasari, Benedhikta Kikky (Prosiding International conference on Information Technology and Business (ICITB), 2018)
This study aims to find out the efforts of street vendors in giving entrepreneurial influence to communities on the border of West Kalimantan, especially in Bengkayang so that they can create business independently. Through this research can also be known how far the community has an entrepreneurial spirit to do business, when work is difficult to obtain in the present, to meet the needs of life so that it is not dependent on others. This research method uses qualitative descriptive method. The research location is in Bengkayang sub-district. The object of this research is street vendors. Information obtained through observation, interviews and documentation. The results of this study are to find out the efforts of street vendors in motivating the community in creating business opportunities.Keywords: Business, Street Vendors, Entrepreneurship